Conservative versus surgical treatment for Garden I hip fracture: A randomized controlled trial protocol. Issue 52 (24th December 2020) - Wang, Wei; Xu, Fangzhu; Luo, Jianguang; Zhu, Liping
Abstract: Background: A femoral neck fracture (FNF) is one of the most destructive and familiar injuries encountered via the orthopedic surgeons. However, this is no guideline for the treatment of the Garden I hip fractures because the current evidence is limited from the poor study design and small sample size. The objective of our research is to compare the safety and effectiveness of the surgical treatment and conservative treatment in the non-displaced FNFs. Methods: This is a randomized trial, which will be implemented from December 2020 to December 2021. The experiment was granted through the Research Ethics Committee of the Zhenhai District People's Hospital of Ningbo (2014005). Hundred patients meet inclusion criteria and exclusion criteria are included. Patients who are eligible for the following conditions will be included: those over 75 years old with Garden I hip fractures diagnosed by CT or X-ray. Patients with the following conditions will be excluded: patients age under 75 years old, the avascular necrosis of the femoral head, pathological fracture, infection, former symptomatic hip pathology, the history of hip fracture, as well as the lower limb deformity. The primary outcome contains pain at 1 month, 3 months and 6 months and hip function at 1 month, 3 months and 6 months. Secondary outcome includes the life quality, mortality rate, complications such as deep venous thrombosis, pulmonary embolism. Results: Comparison of outcome indicators in 2 groups after conservative treatment or surgical treatment (Table). Conclusion: The current trial will offer better evidence for the future treatment selection for Garden 1 FNFs for patients older than 75years old. Trial registration number: researchregistry6147.